Pengaruh Lingkungan Keluarga Terhadap Kepribadian Anak Di Desa Waringinsari Barat Tahun 2020 - Ningsih, Yeni Yulia; Palupi, Rini; Kusuma, Anggi (Wellness And Healthy Magazine, 2021)
The family is the first ward to shape the character and attitude of a child. According to Slameto (2010). The family environment is the first and foremost influence of one's life, growth, and development. The family environment is the oldest educator, informal, first and foremost experienced by children and educational institutions that parents are responsible for maintaining, caring, protecting and educating children to grow and develop well (Hasbullah, 2009). The term personality or in English Personality comes from Ancient Greek, prosopon or persona meaning "mask" and is commonly used in theatrical performances. The method in the preparation of this article is the critical Review article five-year full text which is from the year 2010-2020 in Bahasa Indonesia and English that meet the criteria PICO and SPIDER. Due to article limitations, quantitative studies were used to get more accurate review results. Search the Google Scholar databases, National Library of the Republic of Indonesia, PubMed, Proquest with the keyword "family environment" "personality" to get articles that fit the topic and purpose. From the results of the study can be concluded that there is the influence of family environment and the condition of the family environment to the child's personality is the better the family environment then Semakian well also child personality. Therefore parents have to model the good that the child will follow.